Prevalence of Non-Albicans Candida Among the Patients Attending a Tertiary Care Hospital in Kathmandu, Nepal - Sharma, Manisha; Pant, Narayan Dutt; Pandey, Pratikshya (Nepal Journal of Biotechnology, 2016)
The main objective of this study was to determine the prevalence of non-albicans Candida among the patients attending a tertiary care hospital in Kathmandu, Nepal. Candida spp. isolated from different clinical samples (sputum, urine, vaginal swab, blood, endotracheal (ET) secretion, pus) from 250 patients between the period of February 2013 and December 2015 were included in the study. Of those 250 patients, 20% were immunocompromised. Sabouraud dextrose agar was used for the isolation of Candida spp. and the identification was performed on the basis of colony morphology, Gram’s stain, India ink preparation, germ tube test, temperature tolerance test, characteristic color change in CHROMagar, chlamydospore production, sugar fermentation test and sugar assimilation test.Out of total 300 Candida spp., majority were isolated from sputum (43.33%) followed by urine (40%) and vaginal swab (6.67%). Of total 151 (50.33%) non-albicans Candida, the most common species isolated were C. tropicalis (62.25%) followed by C. glabrata (23.84%). High prevalence of non-albicans Candida among the patients attending a hospital in Kathmandu, Nepal was noted.